2021
DOI: 10.1177/1049909121991522
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Palliative Care, Hospice Care, and Advance Directives in a Racially and Ethnically Diverse Sample of California Adults

Abstract: Background: Numerous studies have documented multilevel racial inequalities in health care utilization, medical treatment, and quality of care in minority populations in the United States. Palliative care for people with serious illness and hospice services for people approaching the end of life are no exception. It is also well established that Hispanics and non-Hispanic Blacks are more likely than non-Hispanic Whites to have less knowledge about advance care planning and directives, hospice, and palliative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…This mistrust can lead to under-utilization of health care services, a lack of satisfaction with available services or providers, low adherence to medical advice, and reduced compliance with recommended health behaviors [ 18 , 19 ]. Racial disparities and other impacts of racism have been linked to rates of medical mistrust [ 20 22 ]; as such, higher perceived discrimination correlates with higher medical mistrust [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This mistrust can lead to under-utilization of health care services, a lack of satisfaction with available services or providers, low adherence to medical advice, and reduced compliance with recommended health behaviors [ 18 , 19 ]. Racial disparities and other impacts of racism have been linked to rates of medical mistrust [ 20 22 ]; as such, higher perceived discrimination correlates with higher medical mistrust [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study found a positive association between age and hospice awareness among the participants. Although limited evidence on such an association exists in prior studies, a recent study by Bazargan et al 39 also found age was significantly associated with hospice awareness. As of 2018, most hospice care recipients were aged 65 or older, consisting of almost 84% of the Medicare Hospice Benefit beneficiaries.…”
Section: Discussionmentioning
confidence: 94%
“…Healthcare professionals should tailor the information to the rural residents' level of health literacy and discuss it with them in a culturally sensitive way. 39 Also, partnering with community stakeholders and liaisons (eg patients, family, and pastors of local churches) can help identify the most effective forms and venues for the dissemination of hospice information. 39,52,53 Such information cannot be provided only in the written format: interactive, verbal communications accompanied with informational brochures to take home may be more effective in promoting rural residents' hospice awareness than written materials alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this fear can be reduced to prepare for and understand death properly. The process of preparing for death, such as ACP, differs between societies and cultures [6]. A multidisciplinary Delphi panel defined ACP as "a process that supports adults at any age or stage of health in understanding and sharing their personal values, life goals, and preferences regarding future medical care" [7] The purpose of ACP is to make decisions or choose preferences about the planning and use of hospice-palliative care.…”
Section: Discussionmentioning
confidence: 99%